Orthophosphate ion adsorption onto raw shrimp shells - Abidar, Fatiha; Morghi, Mohamed; Abali, M’hamed; Sinan, Fouad; Chiban, Mohamed; Eddaoudi, Hassan; Zebret, Mohamed (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2016)
The aim of this work was to develop new low-cost adsorbents obtained from animal origins, available in large quantities and environmentally friendly. Raw shrimp shell (RSS), a biomaterial of animal origin, is abundant, available, renewable and non-toxic. It has physicochemical properties that can induce a significant adsorptive activity. In this study, the removal of phosphate anions (H2PO4-, HPO42-) from aqueous solution by adsorption onto raw shrimp shells was studied. The surface micro-morphology of the biomaterial was investigated using scanning electron microscope and qualitative element composition was analyzed using energy dispersive X-ray and infrared spectroscopies. The efficiency of the biomaterial was investigated using a batch adsorption technique under different experiment conditions, achieved by varying parameters such as adsorbent dosage, the contact time, the initial phosphate anion concentrations, the temperature and the initial solution pH. Results show that the kinetics adsorption of phosphate ions by the biomaterial is relatively quick and the biomaterial showed a high adsorption capacity of 0.20 g∙g-1 and 0.4 g∙g-1 for HPO42- and H2PO4-, respectively. The adsorption data were analyzed using the Langmuir, Freundlich and Temkin adsorption isotherms to determine the nature of the adsorption sites. Both Langmuir and Freundlich adsorption models showed good fits to the experimental adsorption data.